1995
DOI: 10.1136/jcp.48.5.420
|View full text |Cite
|
Sign up to set email alerts
|

Observer reliability in assessing placental maturity by histology.

Abstract: Aims-To evaluate the ability of five experienced perinatal pathologists to assess placental maturity reliably by histology. Methods-Twenty four haematoxylin and eosin slides, six each from placentas of 27, 31, 35, and 39 weeks' gestation, were circulated to five pathologists on three separate occasions. The slides were labelled with the correct or incorrect gestational ages. Results-The mean absolute error over all 360 readings was 2-72 weeks. Only 54% of the slides were assessed within two weeks of the correc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 9 publications
1
25
0
Order By: Relevance
“…However, a second indicator of MV, villous infarction, was not increased. Estimation of villous maturation is highly variable among pathologists so different thresholds for diagnosis might explain the discrepancy [27]. Alternatively, our inclusion of both advanced villous maturation and villous infarction in the MV category may account for this apparent disagreement.…”
Section: Discussionmentioning
confidence: 75%
“…However, a second indicator of MV, villous infarction, was not increased. Estimation of villous maturation is highly variable among pathologists so different thresholds for diagnosis might explain the discrepancy [27]. Alternatively, our inclusion of both advanced villous maturation and villous infarction in the MV category may account for this apparent disagreement.…”
Section: Discussionmentioning
confidence: 75%
“…It is therefore possible that the pathologic diagnosis of PVH may be biased the closer delivery is to 37 weeks. This potential bias has been studied by Khong et al [35] who have shown that the magnitude and direction of error when assessing placental maturity is actually less after 31 weeks gestation than earlier, with a relative underestimation of gestational age in later preterm deliveries [31]. Gestational age was tightly controlled in our case series [33] and the pathologist’s diagnosis was made while blinded to gestational age, which is important to reduce bias [31].…”
Section: Discussionmentioning
confidence: 92%
“…Our specific definition requiring that the PVH diagnosis be made only in preterm deliveries should make this study more reproducible, because pathologists can reliably distinguish mature term from preterm villous architecture [32]. This is important because although others have reported significant differences in placental villous architecture associated with PTB [2530], the reproducibility of these associations has been questioned [31]. Our strict preterm definition, together with our evaluation for distal villous hypoplasia, and the strength of our tightly controlled multicenter trial, reinforces prior studies from the 1990s [20,27], suggesting that placental insufficiency may cause idiopathic PTB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AVM was more likely to occur after 34 weeks' gestation in our study, which raises the potential of false-positive gestational aging bias. However, Khong et al (39) found that the magnitude and direction of error when assessing placental maturity are actually less after 31 weeks' gestation, with a relative underestimation of gestational age rather than overestimation. Therefore, PTL may fall within a continuum of placental insufficiency phenotypes that also include some cases of preeclampsia and FGR.…”
Section: Placental Insufficiency and Ptlmentioning
confidence: 96%